Isolation of Listeria monocytogenes from fish intestines and RAPD analysis - Ertas, HB; Seker, E (Tubitak Scientific & Technological Research Council Turkey, 2005)
One hundred and fifty fish caught from Keban Dam Lake were examined for the presence of Listeria monocytogenes. A random amplified polymorphic DNA (RAPD) assay using a random primer was performed to detect genetic variations among L. monocytogenes isolates. The selective enrichment procedure followed by selective isolation was used for listeria isolation from fish intestines. Ten (6.6%) L. monocytogenes were isolated and identified from fish intestines. Two different band profiles were obtained by the RAPD analysis of the isolates. The results indicated that the isolates might have originated from different sources, and fish contaminated with L. monocytogenes may cause serious health problems in humans.
Keywords: fish; intestine; Listeria monocytogenes; RAPD